2017
DOI: 10.1353/eca.2017.0019
|View full text |Cite
|
Sign up to set email alerts
|

Business Tax Burdens and Tax Reform

Abstract: Tax reforms affect economic performance by changing incentives for business formation, expansion, and operation. The United States has the highest corporate tax rate among countries with advanced economies, and-despite offering significant additional deductions, exclusions, and tax credits-it imposes the heaviest tax burdens. This paper offers a new measure of corporate tax burdens based on information in tax expenditure budgets; this measure implies that the burden of U.S. corporate taxation in 2017 is equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Many other scholars have been actively promoting corporate tax cuts, but they have different opinions on the ways and effects of tax cuts. For example, Grubert and Altshuler [16] considered that changing the corporate income tax to personal income tax can significantly reduce the corporate tax rate; Hines Jr [17] considered that although the corporate tax rate in the United States provides a large number of additional deductions, tax exemptions, and tax credits, however, it creates the heaviest tax burden; Salaudeen and Atoyebi [18] demonstrated that the effect of tax reform was heterogeneous, which led to an increase or decrease in tax burdens in different industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many other scholars have been actively promoting corporate tax cuts, but they have different opinions on the ways and effects of tax cuts. For example, Grubert and Altshuler [16] considered that changing the corporate income tax to personal income tax can significantly reduce the corporate tax rate; Hines Jr [17] considered that although the corporate tax rate in the United States provides a large number of additional deductions, tax exemptions, and tax credits, however, it creates the heaviest tax burden; Salaudeen and Atoyebi [18] demonstrated that the effect of tax reform was heterogeneous, which led to an increase or decrease in tax burdens in different industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tax burden. A business environment with high tax rates increases organizational financial distress, discourages business establishment and business operation expansion [52], and decreases the amount of investment in non-economic activities, e.g., CSR practices [53,54]. For instance, anecdotes about the high corporate tax burden in emerging economies such as China, Russia, and the Ukraine, abound in the media and in reports [21,55].…”
Section: Infrastructure and Csr: Resource Orchestration Logicmentioning
confidence: 99%
“…On the contrary, tax breaks can provide relief to firms, so that they can introduce innovative CSR activities, which might enable them to undertake environmental product innovations, employee training, and safe production [56]. In this case, corporate resource utilization efficiency is improved to bring about superior performance [52].…”
Section: Infrastructure and Csr: Resource Orchestration Logicmentioning
confidence: 99%
“…Additionally, an average of 22% of the federally collectible revenue in Nigeria from 2012-2015 accrues from firms chargeable under the CITA (FIRS, 2012, [13]), what happens to the tax burden of this single large group of tax payers should be of concern to any government in order to ensure an uninterrupted flow of revenue to maintain and finance development. Hines Jr., J.R. (2017) [14] also observes that taxes on business activities that discourage the formation and expansion of businesses, indeed, Spengel et al (2012) [2]; Hebows, S., Ruf, M., and Weichenvieder, A.J. (2011) [15] find tax to determine how attractive a country is Open Journal of Business and Management as a destination for investments.…”
Section: Introductionmentioning
confidence: 99%
“…sole variable of this study is Tax Burden. Following Hine Jr, J.R. (2017)[14];Anderson, J.F (2013) [20] and several other authors, tax burden is estimated using the Effective Tax Rate (ETR). The concept of ETR developed out of the need to ascertain the actual tax burden borne by tax payers in view of the failure of the Statutory Tax Rate (STR) to effective capture the whole essence of a tax system (NIcodeme, 2001)[31].…”
mentioning
confidence: 99%